Untargeted metabolomics of saliva in pregnant women with and without gestational diabetes mellitus and healthy non-pregnant women - Li, Yueheng; Feng, Yang; Yang, Zhengyan; Zhou, Zhi; Jiang, Dan; Luo, Jun (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: To compare the differences in salivary metabolites between pregnant women with gestational diabetes mellitus (GDM), healthy pregnant women (HPW) and healthy non-pregnant women (HNPW), and analyze the possible associations between the identified metabolites and gingivitis. Method: The study included women with GDM, HPW ,and HNPW (each group n = 9). Saliva samples were collected from all participants, and were analyzed with LC-MS/MS-based untargeted metabolomic analysis. The identified differential metabolites were further analyzed in an attempt to explore their possible associations with periodontal health, and provide evidence for the prevention and treatment of periodontal inflammation during pregnancy. Results: In positive ion mode, a total of 2529 molecular features were detected in all samples, while in negative ion mode, 983 metabolites were detected in all samples. A total of 9 differential metabolites with high confidence levels were identified in both the positive and negative ion modes, including L-isoleucine, D-glucose 6-phosphate, docosahexaenoic acid, arachidonic acid, adenosine, adenosine-monophosphate, adenosine 5'-monophosphate, xanthine and hypoxanthine. Among all pathways enriched by the up-regulated differential metabolites, a largest number of pathways was enriched by 4 differential metabolites, adenosine, adenosine 5'-monophosphate, D-glucose 6-phosphate, and adenosine-monophosphate, and among all pathways enriched by the down-regulated differential metabolites, a largest number of pathways was enriched with 3 differential metabolites L-isoleucine, xanthine, and arachidonic acid. Conclusion: Untargeted metabolomic analysis of saliva samples from pregnant women with GDM, HPW, and HNPW identified 9 differential metabolites with high confidence. The results is similar to findings from previous metabolomics studies of serum and urine samples, which offers the possibility of using saliva for regular noninvasive testing in the population of pregnant women with and without GDM. Meanwhile, the associations between these identified differential metabolites and gingivitis need to be further validated by subsequent studies.